Association between lifestyle factors and thyroid function in young euthyroid adults - Merchan-Ramirez, Elisa (KEAI PUBLISHING LTD, 2025)
Purpose:
The present work examines the associations of dietary habits, sedentarism, physical activity (PA) levels and sleep habits, with thyroid function in young euthyroid adults.
Methods:
A total of 105 young euthyroid adults participated in this cross-sectional study. Thyroid function was determined in fasting conditions (> 6 h). Dietary habits were measured by a food frequency questionnaire and three non-consecutive 24 h recalls, and different dietary intake and patterns were then estimated. The time spent in sedentary, PA levels and sleep habits were objectively measured using a wrist-worn accelerometer.
Results:
Energy and carbohydrate intake were positively associated with thyroid stimulating hormone (TSH) (β = 0.222; R2 = 0.102; P = 0.022 and β = 0.425; R2 = 0.129; P = 0.007 , respectively) whereas fat intake was negatively associated with TSH (β = −0.428; R2 = 0.137; P = 0.004). Energy intake was also positively associated with free triiodothyronine (β = 0.277; R2 = 0.137; P = 0.004). Further, adherence to the Mediterranean diet was negatively related to TSH and free thyroxine (FT4) (β = −0.221; R2 = 0.113; P = 0.020 and β = −0.268; R2 = 0.071; P = 0.007, respectively). Vigorous-intensity and overall PA were negatively associated with FT4 (β = −0.227; R2 = 0.052; P = 0.022 and β = −0.204; R2 = 0.042; P = 0.041, respectively). In contrast, no associations were found between sleep parameters and thyroid function.
Conclusions:
Lifestyle factors such as dietary intake and PA levels seems to be related to thyroid function even in young euthyroid adults.